Analytical Application of Hydrotropic Solubilization in Spectrophotometric Determination of Naproxen in Tablet Dosage Form - Patidar, Ashish (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT A new, simple, safe, accurate and reproducible spectrophotometric analytical method was developed for the quantitative estimation of naproxen in solid dosage form by the novel application of hydrotropic solubilization. The enhancement of solubility of naproxen drug was more than 65 fold in hydrotropic solution (7.5M N,N-dimethyl urea solution) as compared to solubility in distilled water. Therefore, it was thought worthwhile to solubilize this poorly water soluble drug from fine powder of its tablets by this novel hydrotropic solubilization technique and then carry out its spectrophotometric estimation at 317 nm (N,N-Dimethyl urea does not interfere above 260nm). The results of the analysis were validated statistically and by recovery studies. The percent label claims and percent recoveries estimated were close to 100 with low values of standard deviation, percent coefficient of variation and standard error. Thus, the method was accurate providing additional advantage of being cost effective and environment friendly.